Tensile and impact properties of polypropylene/microcrystalline cellulose treated with different coupling agents - Samat, Noorasikin; Marini, Che Dini; Maritho, Muna Athirah; Sabaruddin, Fatimah Atiyah (Taylor and Francis Inc., 2013)
The effects of different coupling agents, silane aminopropyltriethoxysilane and maleic anhydride-grafted polypropylene (MAPP), on the mechanical properties of polypropylene (PP)/microcrystalline cellulose (MCC) composites were determined and compared. The composites with low filler loadings, up to 12 wt.%, were prepared via melt-mixing in a twin screw extruder followed by injection moulding. All composites were characterized by tensile and impact tests. It is observed that the addition of MCC slightly decreased the tensile strength but the MAPP composites showed higher tensile strength than the silane composites. In contrast, the silane improved the Young’s Modulus at higher filler content. Additionally, the impact properties increased with the presence of coupling agents. These results indicate that both coupling agents affected the mechanical properties of the composite in different ways associated with different filler content.